2019
DOI: 10.1073/pnas.1810692116
|View full text |Cite
|
Sign up to set email alerts
|

Age-related inflammation triggers skeletal stem/progenitor cell dysfunction

Abstract: Aging is associated with impaired tissue regeneration. Stem cell number and function have been identified as potential culprits. We first demonstrate a direct correlation between stem cell number and time to bone fracture union in a human patient cohort. We then devised an animal model recapitulating this age-associated decline in bone healing and identified increased cellular senescence caused by a systemic and local proinflammatory environment as the major contributor to the decline in skeletal stem/progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(190 citation statements)
references
References 51 publications
8
169
0
4
Order By: Relevance
“…In advanced age, this inflammatory phase is protracted impeding proper osteoblast differentiation and leading to diminished fracture healing which manifests as delayed bone union, increased rates of re-fracture, failure of orthopedic implants, and nonunion of acute fractures. 1,[5][6][7]10 Here, we present a potentially therapeutic intervention which involves a reversal of inflammaging shortly after injury by actively shifting pro-inflammatory macrophage signaling to anti-inflammatory macrophage using a small molecule naturally occurring in macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In advanced age, this inflammatory phase is protracted impeding proper osteoblast differentiation and leading to diminished fracture healing which manifests as delayed bone union, increased rates of re-fracture, failure of orthopedic implants, and nonunion of acute fractures. 1,[5][6][7]10 Here, we present a potentially therapeutic intervention which involves a reversal of inflammaging shortly after injury by actively shifting pro-inflammatory macrophage signaling to anti-inflammatory macrophage using a small molecule naturally occurring in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic increase in the number of inflammatory cells and the amount of inflammatory cytokines has been linked to dysfunctional cellular differentiation and dysregulated matrix production at the site of tissue injury. 1,2 This phenomenon has been identified as a potential cause of the dysregulated tissue repair and decreased regeneration capacity after acute injury in advanced age. 3,4 Bone fracture healing is one regenerative process hindered by inflammaging.…”
Section: Introductionmentioning
confidence: 99%
“…Further, several groups have recently shown that dysfunction in the niche can lead to skeletal dysfunction. For example, inflammation via enhanced NF-κB and TNFα signaling reduces SSC abundance and function but can be counteracted pharmacologically to rejuvenate SSCs to improve fracture healing in models of aging and diabetes (Josephson et al, 2019;Tevlin et al, 2017). Thus, gaining a better understanding of the niche factors required for healthy SSC biology is an important direction of research.…”
Section: Regulators Of the Ssc Nichementioning
confidence: 99%
“…Age-associated inflammation is the main reason for stem cell dysfunction. This linkage is mediated by NF-kB and another inflammation signaling (116,117). H19 promotes the osteogenic differentiation of osteoblast cells through the MiR-675/smad3 pathway.…”
Section: A Potential Therapeutic Strategy In Aging-related Disease Tmentioning
confidence: 99%